Reciprocal associations between housing instability and youth criminal legal involvement: a scoping review - Lars Almquist; Sarah Cusworth Walker (BMC, 2022)
Abstract Background Youth experiencing homelessness have disproportionate contact with the criminal legal system. This system contact represents a critical inflection point for enhancing risk or opportunities for stabilization; however, the policy and scholarly traditions examining the criminal legal system have not traditionally incorporated housing or other social determinants as a central focus of intervention. Methods We conducted a scoping review using PRISMA-ScR guidelines to examine how the research literature is currently addressing housing within the context of youth involvement in the legal system. Databases searched included PubMed, Web of Science, and Academic Search Complete. Google Scholar was used to identify papers not indexed in the academic databases of interest. Database searches were conducted between September and December 2019 and articles were restricted to those published in English between the year 2000 and 2019. Key study components extracted included demographic information regarding each sample, type of article, study methodology, direction of effects of interest, outcome measures and primary findings, as well as theoretical frameworks engaged by the authors. Results The search results returned 2154 titles for review. After screening all 2154 titles, 75 met eligibility for inclusion. Abstract reviews were conducted for all 75 papers. 36 abstracts met eligibility criteria and underwent full-text review. Ultimately, 29 articles satisfied eligibility criteria and were included in this scoping review. Conclusions Publications are primarily focused on the social epidemiology of risk factors and behaviors determining youth justice contact, but relatively less so on studies of interventions targeting youth delinquency, crime reduction, or recidivism that included housing support. The lack of continuity in theorizing from epidemiology to applied science in this area represents a gap in the literature that is likely reducing the effectiveness of interventions to interrupt patterns of legal system contact for youth. Integrating a public health framework that emphasizes the upstream social determinants leading to contact with the youth justice system would represent a paradigm shift for the field that would have beneficial effects on long term health outcomes for youth.